INTERAKSI SOSIAL MASYARAKAT RUMAH SUSUN SEDERHANA SEWA (RUSUNAWA) REJOSARI KECAMATAN TENAYAN RAYA KOTA PEKANBARU - Purba, Lamtiur Friska N Purba; Ariwandari, Hesti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Abstract            This research was conducted in Kelurahan Bambu Kuning, Tenayan Raya District, Pekanbaru City. The purpose of this study is to find out the interactions in their residents during their stay and settle in a flat. This research focused on the activity in the form of cooperation and forms of conflict and the social relationships that underlie these interaction. The technique on this research was done by determining the samples using census or saturated sampling and set a sample of 49 people. The author uses quantitative descriptive methods and data instruments are observation, questionnaire or questionnaire and documentation. The results of the study showed that the social interaction such as the cooperation’s form on the basis of the same ethnic / ethnic relationship 24.5%, age 16.3%, employment 24.5%, family relations 8.2%, friendship 26.5%, and living in the same block 36.7%. In addition, there are two forms of conflict that have taken place, namely in a quarrel and physical contest. This happens because the environments / yard are dirty, noisy, debt / accounts receivable, and borrowing motorbikes. The level of conflict is commonly found because the environments / dirty yard are 65.3%. And the level of conflict on a physical basis is 22.4% due to debt / receivables.  In this case, it proves that the form of community flats collaboration has not gone very well, more self-closing, and still look at the background of the other person when building their cooperative relations. While some forms of conflict have occurred because some of residents who do not care, uncontrollable anger, disturb the situation of the occupants personal conditions and deny the agreement that has been set. Keywords: Interaction Social, Cooperation, Conflict, Social Relation